PENYELESAIAN MASALAH KONSEP ENERGI PADA GERAK HARMONIK - Eko Sujarwanto (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2016)
ABSTRACTThe purpose of this study was to determine the problem-solving ability in the energy concept of harmonic oscillation. Students were given recognition problem task to determine the recognition ability of physics problem and requested to solve problems based on the problem-solving stage. Interviews were conducted to follow up on studentsâ€™ problem recognition and problem solving. The results showed studentsâ€™ construction of physics concepts have not formed properly,Â students is able to distinguish between simple harmonic motion and damped harmonic motion, and students have difficulty in applying energy-theorem and energy-conservation laws in harmonic oscillation problem. Learning that involves asking the students give a conceptual explanation to the opinions and answer orally or in writing, giving the problem to be grouped based on the concept might can be done to help students establish physic concepts well and solve physics problems. For further research, it should be done involving more students. KEYWORDS: philosophical, concepts Biology education